الميل إلى العنف لدى طلبة عجلون الجامعية في ضوء بعض المتغيرات - الفريحات، باسم محمد; البطاينة، أسامة (جامعة الإمارات العربية المتحدة - كلية التربية, 2015)
هدفت الدراسة الحالية التعرف على درجة الميل إلى العنف لدى طلبة كلية عجلون الجامعية في ضوء بعض المتغيرات، ولهذه الغاية تم تصميم استبانة تكونت من (23) فقرة تقيس مستوي الميل نحو العنف، تم توزيعها على عينة تكونت من (463) طالب وطالبة من كلية عجلون الجامعية تم اختيارهم من الشعب الاختيارية والإجبارية للعام 2014-2015م، وبعد جمع البيانات ومعالجتها إحصائياً أظهرت النتائج وجود درجة منخفضة ودالة إحصائياً على الميل إلى العنف لدى طلبة كلية عجلون الجامعية، ووجود فروق في مستوي الميل إلى العنف تعزى لمتغير النوع ولصالح الذكور، ووجود فروق في مستوى الميل إلى العنف تعزى لمتغير الكلية لصالح الإنسانية، ووجود فروق في مستوى الميل إلى العنف تعزى لمتغير التحصيل الأكاديمي ولصالح التحصيل المنخفض، وعدم وجود فروق على متغير نوع القبول.
This study aimed to identify the degree of the violence trend of Ajloun University College students in light of some of variables. For this purpose, a questionnaire was designed and it consisted of (23) items to measure degree of violence trend and it was distributed to a sample consisting of 463 female and male students of Ajloun University of College for the academic year 2014-2015. The results of the study showed there was a statistically low degree of violence among students of Ajloun University College. There were also differences in the trend level of violence attributed to the gender variable in favor of males, and the existence of differences in the violence trend level attributable to the college variable in favor of the humanitarian stream. There were differences in the level of violence attributed to variable of academic achievement and in favor of the low achievement, but there were no significant differences attributed to the variable of admission type.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الصحة النفسية -- الرعاية الإجتماعية -- مستخلصات الأبحاث -- التعليم الجامعي -- طلاب الجامعات -- كلية عجلون الجامعية -- الأردن